Between valleys, plateaus, and mountains: unveiling livestock altitudinal mobility in the Iron Age Iberian Peninsula (3rd c. BC) through a multi-isotope approach - Messana, Chiara; Tornero, Carlos; Madgwick, Richard; Lamb, Angela L.; Evans, Jane; Colominas, Lídia (Frontiers in Environmental Archaeology, 2023)
Seasonal altitudinal mobility has been a key practice among pastoral societies in the north-eastern Iberian Peninsula to cope with the unpredictable Mediterranean climate. The existence of a massive and regulated mobile herding system in this area dates back to the 12th century. Nevertheless, early herd connections between the lowlands and the Pyrenees during the Roman period have been documented. The available information regarding the potential adoption of sheep's mobile pastoralism by Iberian societies prior to the Romans' arrival is limited. This study aims to provide fundamental new insights into livestock altitudinal mobility during this period through a biogeochemical approach. Sequential analysis of carbon and oxygen isotope values is combined with strontium isotope ratios from sheep second and third lower molars from four Catalan sites (Mas Castellar de Pontós, Tossal de Baltarga, Sant Esteve d'Olius, Turó de la Rovira). The results reveal evidence of migrations across different altitudinal and geological areas, unveiling the great adaptability of mobile livestock strategies by Iberian populations. The first evidence of descending herds' mobility from the Pyrenees to the lowlands prior to the Roman conquest is also attested. Finally, the effectiveness of multi-isotope analysis (δ18O, δ13C, 87Sr/86Sr) in detecting seasonal livestock movements is demonstrated. Thus, this study provides a comprehensive and nuanced understanding of the complexity of sheep livestock management of the north-eastern Iberian societies during the Middle/Late Iron Age. Moreover, the research points to a more integrated and connected Ibero-Pyrenean world with contemporary lowland communities than so far suggested. However, animal mobility was not widely practised and was possibly determined by the environmental conditions, economic needs, and political decisions of each settlement.